Innovative Entrepreneurship as a Collaborative Effort: An Institutional Framework - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2020)
We demonstrate how successful entrepreneurship depends on a collaborative innovation bloc (CIB), a system of innovation that evolves spontaneously and within which activity takes place through time. A CIB consists of six pools of economic skills from which people are drawn or recruited to form part of a collaborative team, which is necessary for innovation-based venturing to flourish. The six pools include entrepreneurs, inventors, early- and later-stage financiers, key personnel, and customers. We show how the application of the CIB perspective can help make institutional and evolutionary economics more concrete, relevant, and persuasive, especially regarding institutional prescriptions. Generally, we envision an institutional framework that improves the antifragility of CIBs and the economic system as a whole, thus enabling individual CIBs and the broader economic system to thrive when faced with adversity.
Keywords: D20; G32; L23; L26; O33; 330; Institutional economics; Evolutionary economics; Antifragility; Entrepreneurship; Innovation; Institutions